The value of Stilbestrol implants for beef cattle - Walker, G.L.; Smith, E.F.; Koch, B.A.; Cox, R.F. (Kansas Agricultural Experiment Station, 2011)
Thirty choice-quality Hereford steer calves from the Williams Ranches near Lovington, N.M., were used in this test. These animals grazed together on dry bluestem pasture. They were separated for a brief period each morning into three groups and fed their different supplements. The supplements fed per head daily were: Lot 1, 1 pound of soybean oil meal pellets; lot 2, 2 pounds of soybean oil meal pellets; and lot 3, 1 pound of soybean oil meal pellets plus 1 pound of ground corn. Six animals in each of the three lots were implanted with 48 mgs. of stilbestrol. Wintering phase. Gains between implants and controls were comparable in lot 1; however, in lots 2 and 3 those implanted gained 0.36 pound and 0.35 pound more per day than did the controls. There were some treated animals that exhibited abnormal secondary sex characteristics and uneven toplines. Grazing phase. All animals were grazed in the same pasture during the summer. Gains between controls and implants were quite similar in all lots. Undesirable appearance due to implanting was still apparent in a few animals.
Keywords: Beef; Stilbestrol; Gain; Protein